Urgensi Kisah Nabi Terhadap Pendidikan Anak Usia Dini - Nur Azizah; Sarah Busyra (Pendidikan Agama Islam, 2021)
The phenomenon occurs in Indonesia is that many people have high reading interest, but have low reading power. This is due to the educational pattern since childhood which the parents did not pay attention to reading habits and also what materials were read. Based on Montessori's theory, children's fantasies must be limited, so she recommends stories based on true stories. In this study, the researchers would like to present recommendations for building reading habits by providing stories of the prophet from an early age as well as its influence on children's cognitive, emotional and spiritual development. This research uses qualitative descriptive phenomenology research. The subjects of this study were two housewives who gave stories of the prophet to their children. The results of this study indicate that the telling of the prophet's story from a child at an early age is an urgent thing for parents to do in order to form a child who is not only good in character, but also mentally and spiritually.